A Moderated Mediation Analysis of Islamic Bank Stability in Asian OIC Countries - Amalia, Shendy; Heryana, Toni; Waspada, Ikaputera; Sari, Maya; Ho, Thuy Tien (Universitas Muhammadiyah Malang, 2026)
Purpose: This study investigates the relationship between asset diversification and Islamic bank stability by incorporating profitability as a mediating variable and managerial ownership as a moderating variable. The study aims to determine whether diversification contributes to financial resilience and whether internal governance mechanisms reinforce this effect. Methodology/approach: Using panel data from Islamic banks in OIC Asian countries during 2020–2024, the analysis applies Hayes’ PROCESS Model 15, allowing the simultaneous examination of mediation and moderation effects within a single analytical framework. Findings: The results show that managerial ownership plays a decisive role in influencing Islamic bank stability, with evidence pointing to a destabilizing governance effect. Conversely, asset diversification and profitability do not demonstrate a meaningful relationship with stability. Additional analysis indicates that profitability does not mediate the diversification stability nexus, and managerial ownership does not condition these relationships. These findings highlight the dominant role of governance incentives over diversification strategies in explaining stability outcomes among Islamic banks. Practical implications: The study enriches the agency–governance discourse in Islamic finance and offers policy insights for strengthening the long-term resilience of Islamic banks. Originality/value: The research introduces a moderated mediation framework integrating diversification, profitability, and managerial ownership using Hayes’ PROCESS Model 15 in the context of OIC Asian Islamic banks.